Cascaded Self-Raman Laser Emitting Around 1.2–1.3 μm Based on a c-cut Nd:YVO4 Crystal - Haiyong Zhu; Junhong Guo; Xiukai Ruan; Changwen Xu; Yanmin Duan; Yaoju Zhang; Dingyuan Tang (IEEE Photonics Journal)
An acousto-optic Q-switched self-Raman laser emitting around 1.2–1.3 μm based on cascaded conversion with the Raman shifts of 259 and 890 cm−1 was demonstrated in a c-cut Nd:YVO4 crystal. The laser starts with single Stokes emission at 1215 nm. As the incident pump power is increased, Stokes emissions at 1255 and 1316 nm also appear in sequence. When the incident pump power reaches 17.1 W and the pulse repetition frequency is set at 10 kHz, multi-Stokes output is obtained, and the average output power of the laser is 1.02 W, corresponding to a slope efficiency of 9.1%. The multi-Stokes laser output has a pulsewidth of 5.2 ns. Therefore, self-Raman laser lines were enriched with the participation of small Stokes shift of 259 cm−1 in the c-cut Nd:YVO4 crystal.